Liver transplantation after radioembolization in a patient with unresectable HCC - Moreno Luna, Laura E. (2009)
BACKGROUND: A 58-year-old white man who was being followed by his hepatologist for nonalcoholic steatohepatitis-related liver cirrhosis and portal hypertension and who had been found to have a biopsy-proven hepatocellular carcinoma (HCC) on routine screening, self-referred to our center for a second opinion on the management of his HCC. INVESTIGATIONS: Laboratory investigations, CT scan of the abdomen and chest, bone scan and technetium macroaggregated albumin scan. DIAGNOSIS: The patient had unresectable HCC. MANAGEMENT: The patient underwent two treatments with Yttrium-90 glass microspheres, which were performed as outpatient procedures 1 month and 3 months after diagnosis. He underwent orthotopic liver transplantation (OLT) 1 year after the initial diagnosis of HCC. The post-OLT immunoregimen included OKT3 plus rituximab and high-dose steroids. On discharge from hospital he was on immunosuppressive treatment with tacrolimus. He had de novo autoimmune hepatitis 6 months post-OLT, which was treated with a short course of low-dose steroids and addition of mycophenolate mofetil.